Integración de funciones irracionales (1)

RESUMEN TEÓRICO
    Enunciado
  1. Calcular $\displaystyle\int\frac{dx}{\sqrt{3x+1}-\sqrt[4]{3x+1}}.$
  2. Calcular $\displaystyle\int\frac{x^3\;dx}{\sqrt{x+2}}.$
  3. Calcular $I=\displaystyle\int\frac{dx}{(2x-5)^{2/3}-(2x-5)^{1/2}}.$
    Solución
  1. Si $t^4=3x+1,$ entonces $4t^3dt=3\;dx,$ por tanto: $$\begin{aligned}& \displaystyle\int\frac{dx}{\sqrt{3x+1}-\sqrt[4]{3x+1}}=\frac{4}{3}\int\frac{t^3\;dt}{t^2-t}=\frac{4}{3}\int\frac{t^2\;dt}{t-1}\\&=\frac{4}{3}\int\left(t+1+\frac{1}{t-1}\right)dt=\frac{4}{3}\left(\frac{t^2}{2}+t+\log \lvert t-1\rvert\right)+C\\&=\frac{2}{3}\sqrt{3x+1}+\frac{4}{3}\sqrt[4]{3x+1}+\lvert \sqrt[4]{3x+1}-1\rvert+C.
    \end{aligned}$$
  2. Si $t^2=x+2,$ entonces $2t\;dt=dx,$ por tanto: $$\begin{aligned}&\int\frac{x^3\;dx}{\sqrt{x+2}}=2\int\frac{(t^2-2)^3t\;dt}{t}=2\int (t^2-2)^3\;dt=\\
    &=2\int (t^6-6t^4+12t^2-8)\;dt=2\left(\frac{t^7}{7}-\frac{6t^5}{5}+4t^3-8t\right)+C.
    \end{aligned}$$ Sustituyendo $t=\sqrt{x+2}$ y simplificando: $$\int\frac{x^3\;dx}{\sqrt{x+2}}=\frac{2\sqrt{x+2}}{35}\left(5(x+2)^3-42(x+2)^2+140(x+2)-280\right)+C.$$
  3. Si $t^6=2x-5,$ entonces $6t^5\;dt=2\;dx,$ por tanto: $$\begin{aligned}&I=\displaystyle\int\frac{dx}{(2x-5)^{2/3}-(2x-5)^{1/2}}=\displaystyle\int\frac{3t^5dt}{t^4-t^3}=3\int\frac{t^2dt}{t-1}=\\
    &=3\int\left(t+1+\frac{1}{t-1}\right)dt=\frac{3t^2}{2}+3t+3\log\lvert t-1\rvert+C.
    \end{aligned}$$ Sustituyendo $t=(2x-5)^{1/6}:$ $$I=\frac{3\sqrt[3]{2x-5}}{2}+3\sqrt[6]{2x-5}+3\log\lvert \sqrt[6]{2x-5}-1\rvert+C.$$
Esta entrada fue publicada en Cálculo/Análisis. Guarda el enlace permanente.